The Hydrogen Evolution Reaction in Alkaline Solution: From Theory, Single Crystal Models, to Practical Electrocatalysts - Zheng, Yao; Jiao, Yan; Vasileff, Anthony; Qiao, Shi‐Zhang (Angewandte Chemie International Edition, 2018)
The hydrogen evolution reaction (HER) is a fundamental process in electrocatalysis and plays an important role in energy conversion for the development of hydrogen‐based energy sources. However, the considerably slow rate of the HER in alkaline conditions has hindered advances in water splitting techniques for high‐purity hydrogen production. Differing from well documented acidic HER, the mechanistic aspects of alkaline HER are yet to be settled. A critical appraisal of alkaline HER electrocatalysis is presented, with a special emphasis on the connection between fundamental surface electrochemistry on single‐crystal models and the derived molecular design principle for real‐world electrocatalysts. By presenting some typical examples across theoretical calculations, surface characterization, and electrochemical experiments, we try to address some key ongoing debates to deliver a better understanding of alkaline HER at the atomic level. Focusing on the long‐lasting debates surrounding the activity descriptor for the electrocatalytic hydrogen evolution reaction in alkaline conditions, some fundamental studies, from theoretical computations and surface electrochemistry on single crystal models, to practical electrocatalysts with large surfaces, are summarized.